Perancangan Sistem Monitoring Ketinggian Air Pada Tangki Soft Water Menggunakan Sensor Ultrasonik Hc-Sr 04 di PT Tirta Investama Plant Citeureup - Kusuma, Adillah Surya; Saragih, Yuliarman (Peneliti.net, 2025)
Monitoring is the process of collecting data and analyzing information from the implementation of a program, including regular checks to see if the activities/program are running according to plan, so that any observed or encountered issues can be addressed. The current procedure for checking the water level in the reservoir tanks has several weaknesses, one of which is that the tanks are often located on the roofs of houses, making it difficult to monitor the water level. One solution to this problem is to monitor the water using a resistance wire. However, using a resistance wire can affect its value due to the compounds present in the water. Another solution is to use an ultrasonic sensor because ultrasonic sensors are capable of measuring water levels with an average measurement error of 93%. This prompted the development of an Android-based mobile application equipped with an Arduino and its components to monitor the water level in the tank. The Arduino device is installed on the top of the tank, and the HC-SR04 ultrasonic sensor is facing the inside of the tank. The HC-SR04 ultrasonic sensor will work to measure the water level inside the tank